Referat Radiology Emergency : Fraktur Regio Thorak - Ummi Issayyidah; Muhammad Azmi (Lembaga Pengembangan Kinerja Dosen, 2025)
Emergency situations can come from trauma or non-trauma. Fracture is a term for total or partial loss of continuity of bone, cartilage, usually caused by trauma. Fracture is a condition where there is an incontinuity in bone integrity. Thoracic trauma causes 20% of all deaths due to trauma. The radiological modalities that play the biggest role in emergency cases are plain photo/radiography, ultrasound (ultrasound), and computerized tomography (CT-Scan). Magnetic Resonance Imaging (MRI) or nuclear medicine can in many cases provide more accurate results. Some emergency thoracic fractures are costae, sternum and vertebrate fractures.